P15.03 Development of a new cem reporter t-cells (gxr-cells) viral inhibition assay (via) for elucidating the role of class-i-hla alleles on the inhibitory capacity of hiv-1-specific cd8+t-cells. (13th September 2015) - Ogunshola, F; Mewala, N; Wright, JK; Ismail, N; Brockman, MA; Walker, BD; Ndung'u, T; Ndhlovu, ZM
Abstract : Introduction: Standard immunogenicity assays, such as ELISpot and intracellular cytokine staining, fail to correlate HIV-1-specific CD8 + T-cells responses with HIV-1 replication in-vivo . Therefore, it is essential to develop assays that can determine antiviral potential of vaccine elicited CD8 + T-cells. The current ELISA-VIA measures HIV-1-p24 production overtime in autologous CD4 + T-cells. However, it is not designed to identify the class-I-HLA-allele involved in mediating the response. We developed a new FACS based VIA that can investigate CD8 + T-cells antiviral potential in the context of restricting class-I-HLA alleles. The assay measures the ability of CD8 + T-cells to kill HIV-1 infected GXR-cells over-expressing class-I-HLA allele of interest. The assay utilises a GXR-cell engineered to express GFP upon HIV-1 infection. Methods: CD8 + T-cells were co-cultured with HIV-1 infected GXR-cells for 3 days. Reduction in the infected GXR-cells expressing GFP measured by FACS was used to evaluate the CD8 + T-cells killing activity. The assay was validated using a panel of 9 HIV-infected samples and were concurrently assayed with the ELISA-VIA. The tested results on each assay were categorised into four groups namely: true-inhibition (TI ≥50%), doubtful-inhibition (DI ≥20% to ≤49.99%), false-inhibition (FI ≥10% to ≤19.99%) and non-inhibition (NI≤ 9.99%). These results were used in a 2 by 2 table to compute sensitivity (TI/TI+DI) and specificity (FI/FI+NI). Results: True inhibition was observed in 44% of samples analysed using GXR-VIA compared to 33% with ELISA-VIA. 11% with GXR-VIA had doubtful result compared to 33% with ELISA-VIA. 22% with GXR-VIA were categorised as false inhibition compared to 33% with ELISA-VIA. Interestingly, no sample showed non-inhibition with GXR-VIA whereas 22% showed no inhibition by ELISA-VIA. Collectively, GXR-VIA is very specific (100%) but less sensitive (57%) at detecting virus inhibition activity. Conclusion: The specificity of GXR-VIA and its marginal sensitivity indicates that the assay is capable of identifying CD8 + T-cells-mediated inhibition of HIV-1 replication. Overall, the GXR-VIA provides a platform to assess the influence of different restricting class-I-HLA alleles on HIV-1-specific CD8 + T-cells antiviral function.